2007
DOI: 10.1093/heapol/czm002
|View full text |Cite
|
Sign up to set email alerts
|

Lessons learned from bednet distribution in Central Mozambique

Abstract: This project failed to achieve adequate or equitable levels of ITN coverage in a timely manner in the programme sites. However, its findings helped support a subsequent Mozambican decision to conduct targeted distribution of long-lasting nets to the neediest populations in the provinces where the project was conducted.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
24
0
1

Year Published

2007
2007
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 17 publications
(26 citation statements)
references
References 22 publications
1
24
0
1
Order By: Relevance
“…Although the multivariate analysis takes into account the effects of other distribution systems, we cannot rule out potential confounding by other factors that changed during the time the programme roll out occurred. Secondly, for some districts there is no true baseline measure of coverage: [36][37][38] the consistent gap between use of any net and use of a treated net suggests an urgent need to improve insecticide treatment of nets. The treatment gap has persisted despite considerable investment by the SMARTNET project in communications activities promoting net treatment and retreatment as well as efforts to work with manufacturers to ensure bundling of all nets with insecticide treatment kits.…”
Section: Discussionmentioning
confidence: 99%
“…Although the multivariate analysis takes into account the effects of other distribution systems, we cannot rule out potential confounding by other factors that changed during the time the programme roll out occurred. Secondly, for some districts there is no true baseline measure of coverage: [36][37][38] the consistent gap between use of any net and use of a treated net suggests an urgent need to improve insecticide treatment of nets. The treatment gap has persisted despite considerable investment by the SMARTNET project in communications activities promoting net treatment and retreatment as well as efforts to work with manufacturers to ensure bundling of all nets with insecticide treatment kits.…”
Section: Discussionmentioning
confidence: 99%
“…Although a younger generation of researchers favoured ITNs, they had little influence on decisions about which intervention to use: “Within the MoH, the older experts are very much in favour of spraying and the younger ones like spraying, but they would also like to see other methods of control used.” (Researcher, Mozambique) Researchers were, however, able to influence policy on net pricing by producing research evidence (Dgedge 2000; Brentlinger et al 2007). In South Africa, there was much greater reliance on the Malaria Advisory Group, a body set up by the National Department of Health:

“We felt that we needed to bring and call on expertise from the country to advise us on policy—and that’s the main reason why the decision was taken to put an advisory group together.” (Government official, South Africa)

The Malaria Advisory Group discussed ITNs and research was commissioned on their effectiveness, in comparison with IRS (Mnzava et al 1999).…”
Section: Resultsmentioning
confidence: 99%
“…The trial comparing IRS and ITNs (which showed similar results for both interventions) had been started (Goodman et al 2001), but was stopped early owing to a malaria epidemic that was seen to demand immediate intervention. In Mozambique, the involvement of researchers in the production of evidence around ITN pricing helped create a sense of local ownership (Dgedge 2000; Brentlinger et al 2007). …”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations